Phytochemical composition and cytotoxic assessment of Carica papaya leaf extracts on human squamous carcinoma-3 Cells (in vitro): a laboratory experimental - Roeslan, Moehamad Orliando; Rahma, Syafira Fayza; Kokilakanit, Paopanga (Padjadjaran Journal of Dentistry, 2025)
Introduction: Oral cancer is one of the major diseases that can cause death worldwide. With the advancement of research on new drugs, medicinal plants have been explored as an alternative approach to cancer treatment. Papaya (Carica papaya) is a plant that has long been used in traditional medicine to treat various diseases. Ethanolic and aqueous extracts of C. papaya leaf have been reported to exhibit anticancer properties through mechanisms such as inhibiting cell proliferation and inducing apoptosis. This study aimed to analyze the cytotoxic effect of C. papaya leaf extract obtained with different extraction solvents on HSC-3 cell lines. Methods: This laboratory-based experimental study employed a post-test only control group design. The sample size was determined using the Federer formula, yielding four replicates per group. HSC-3 cell lines were treated with ethanolic and aqueous extracts of C. papaya leaf at concentrations of 125, 250, and 500 μg/mL for 24 hours, followed by a cytotoxicity test using the CCK-8 assay. Data were analyzed using one-way ANOVA followed by Tukey’s post hoc test. Results: Phytochemical analysis revealed the presence of alkaloids, flavonoids, and tannins in both ethanolic and aqueous extracts, whereas triterpenoids were detected only in the ethanolic extract, and saponins were detected only in aqueous extract. HSC-3 cells did not show any significant cytotoxic response to either extract at any tested concentration. Conclusion: Ethanolic and aqueous extracts of C. papaya leaf at concentrations of 125, 250, and 500 μg/mL did not exhibit any cytotoxic effects on HSC-3 cell lines.